2023
DOI: 10.3390/nu15194175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Ingestion of Bifidobacteria and Dietary Fiber on Improvement in Cognitive Function: A Randomized, Double-Blind, Placebo-Controlled Trial

Naoki Azuma,
Takashi Mawatari,
Yasuo Saito
et al.

Abstract: Bifidobacterium animalis subsp. lactis GCL2505 has been shown to have some positive effects on health, including improved defecation frequency and reduced visceral fat. These effects are thought to be due to GCL2505′s unique ability to reach the intestine in a viable form and proliferate after a single intake. This leads to an increased number of intestinal bifidobacteria. This randomized, double-blind, placebo-controlled, parallel-group study was conducted to confirm that intake of GCL2505 and inulin (a prebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In our review of the literature, we found that probiotic/prebiotic/symbiotic supplementation, administered for a minimum of 4 weeks (up to a maximum of 6 months), resulted in a significant improvement ( p < 0.05) in cognitive performance among healthy aging individuals (over 60 years old) (see Table 2 ). This improvement was observed in various domains, including memory, attention, and visuospatial/constructional abilities [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, one study [ 27 ] did not find a significant improvement in cognitive performance due to probiotic supplementation, specifically in seniors (average age 64.3 years) who were physically active and met recommended exercise guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In our review of the literature, we found that probiotic/prebiotic/symbiotic supplementation, administered for a minimum of 4 weeks (up to a maximum of 6 months), resulted in a significant improvement ( p < 0.05) in cognitive performance among healthy aging individuals (over 60 years old) (see Table 2 ). This improvement was observed in various domains, including memory, attention, and visuospatial/constructional abilities [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, one study [ 27 ] did not find a significant improvement in cognitive performance due to probiotic supplementation, specifically in seniors (average age 64.3 years) who were physically active and met recommended exercise guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of visceral fat induces chronic inflammation. Recent studies have reported that intake of GCL2505 and inulin suppresses chronic inflammation, thereby improving cognitive and vascular function [58,59]. Further research is needed to determine the mechanism by which the intake of GCL2505 and inulin suppresses chronic inflammation by suppressing visceral fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics could also affect cognitive functions. For example, Azuma et al [23] studied the effect of a beverage containing inulin on Japanese women or men (50-80 years) and assessed biochemical and immunological parameters, the quali-quantitative compo-sition of the microbiota of fecal samples, the cognitive functions through Cognitrax (a computer-based battery of cognitive function tests), and quality of life on eight scales (physical functioning, role physical, bodily pain, general health perceptions, vitality, social functioning, role emotional, and mental health); the results revealed the improvement in the scores of three domains of cognitive functions (attention, flexibility, and executive functions), probably linked to an increase in bifidobacteria and to a slight modulation of some inflammatory markers.…”
Section: Cognitive Functionsmentioning
confidence: 99%